2001
DOI: 10.1523/jneurosci.21-24-09585.2001
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Ca2+-Activated K+Channels in Glutamatergic Hippocampal Terminals and Their Role in Spike Repolarization and Regulation of Transmitter Release

Abstract: Large-conductance Ca 2ϩ -activated K ϩ channels (BK, also called Maxi-K or Slo channels) are widespread in the vertebrate nervous system, but their functional roles in synaptic transmission in the mammalian brain are largely unknown. By combining electrophysiology and immunogold cytochemistry, we demonstrate the existence of functional BK channels in presynaptic terminals in the hippocampus and compare their functional roles in somata and terminals of CA3 pyramidal cells. Doublelabeling immunogold analysis wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
303
3
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 307 publications
(337 citation statements)
references
References 65 publications
29
303
3
2
Order By: Relevance
“…Current through these channels contributes to the early AHP, prolongs the refractory period, and limits repetitive firing. Additionally, BK current shortens AP duration by accelerating repolarization, thereby limiting the amount of Ca 2+ influx during an AP and thereby decreasing neurotransmitter release [38,72,75]. Our methods characterizing I K(Ca) in sensory neurons adds validity to these previous findings by using methods that employ a natural AP waveform stimulus in one case, and by controlling cytoplasmic Ca 2+ levels in the other.…”
Section: Discussionsupporting
confidence: 53%
“…Current through these channels contributes to the early AHP, prolongs the refractory period, and limits repetitive firing. Additionally, BK current shortens AP duration by accelerating repolarization, thereby limiting the amount of Ca 2+ influx during an AP and thereby decreasing neurotransmitter release [38,72,75]. Our methods characterizing I K(Ca) in sensory neurons adds validity to these previous findings by using methods that employ a natural AP waveform stimulus in one case, and by controlling cytoplasmic Ca 2+ levels in the other.…”
Section: Discussionsupporting
confidence: 53%
“…BK channels are positioned to react to action potential-triggered Ca 2+ influx. Electrophysiological approaches indicate that BK channels can control glutamate release under conditions of excessive neuronal activity (Gribkoff et al, 2001a;Hu et al, 2001;Yamashita et al, 2006). Functionally, a deficit in axonal or presynaptic BK channels might render mossy fibers hyperexcitable during epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The precise distribution and preferential trafficking of BK channels to axon terminals and somatodendritic regions can ultimately determine the function of BK channels in neurons and circuits. For instance, in hippocampal pyramidal neurons, BK channels are trafficked to presynaptic membranes where they are thought to modulate glutamatergic neurotransmission in conditions of excessive excitability (Hu et al, 2001). Nevertheless, in many neurons, BK channels also contribute to the action potential repolarization and to the fast afterhyperpolarization thereby influence additionally the neuronal firing frequency (Shao et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cAMP analogues [in M: 100 cAMP or 100 8 chlorophenylthio (CPT)-cAMP] in the intracellular medium in the recording pipette (Madison and Nicoll, 1986). The SK channels are known to be predominately resistant to these drug concentrations (Ishii et al, 1997;Wang et al, 1998;Hu et al, 2001), but evidence for a small cAMP-induced increase of I aAHP has been reported (Stocker and Pedarzani, 2000). The blockade of non-SK K ϩ channels also served to increase the cell input resistance, thereby facilitating the activation of voltage-gated Ca 2ϩ channels and, hence, Ca 2ϩ influx and SK channel activation and improving the space clamp of the cell.…”
Section: Functional Expression Of Sk Channels In Rat Brainmentioning
confidence: 99%